A parassubordinação e as metamorfoses do direito do trabalho para uma nova era colaborativa - Leticia Mara Pinto Ferreira (2013)
This dissertation examines the main changes in the conjuncture workforce originally recognized that lead the challenging transition from traditional economies to hightech smart companies, whose advent represents a new lateral and collaborative era. Concurrently with the perspective of collaborative behavior, labor law undergoes a retraction movement in its many aspects, including motivated by the appearance of the European parasubordination work, erected under the misguided premise of classic subordination, and the emergence of various working relationships that represent a process of endless metamorphoses. This arena presents itself as a huge prophecy, reason why the proposed research does not aim at providing a definitive answer to the issue. The fundamental task of the research is to leverage changes already institutionalized to support criticism of current frameworks and print contributions on its behalf, always thinking about the work as an extended global element, which includes not only the production process, but the prominent human factor.